Knowledge, Attitude and Practices Towards COVID-19 Among Grass-Root Level Workers of Bengaluru District - A Cross-Sectional Study - Lavanya R; Usha Rani S Padmanabha; Dhaheera Dheeshan; Renuka Venkatesh (RGUHS National Journal of Public Health)
Introduction Coronavirus disease 2019 COVID-19 is a re-emerging infectious disease that has caused loss of human lives economic repercussions and increased poverty. COVID-19 was declared a pandemic and an infectious disease of public health concern the role of community health workers particularly Accredited Social Health Activists ASHAs became increasingly vital in disseminating awareness about disease transmission and its control measures in the community.Objectives To assess the knowledge attitude and practice of ASHA workers towards COVID-19.Methods A cross-sectional study was conducted among ASHAs working in public health centers PHCs in North Bengaluru over a period of one year. All ASHAs were interviewed using a semi-structured questionnaire to assess their knowledge attitudes and practices KAP regarding COVID-19. A total of 503 ASHAs were selected using a universal sampling technique after obtaining informed verbal consent.Results Among the 503 ASHA workers surveyed 62.2 ASHAs belonged to Bangalore Urban and 37.8 belonged to Bangalore Rural areas. They were aged between 21 and 30 years and 235 of them had five years of experience. An assessment of awareness regarding COVID-19 showed that 502 99.8 participants were aware of the investigations available to diagnose COVID-19 293 58.3 agreed that checking temperature once a day was sufficient and 487 96.8 reported practicing social distancing to prevent the spread of the disease. Conclusion ASHAs showed adequate knowledge attitude and practice towards COVID-19 infection. Proper guidance and adequate training of our grassroots-level workers can significantly enhance their preparedness for future pandemic emergencies.